Evaluating Speed, Agility, and Endurance in Individual and Team Sports: A Comparative Approach - Bitoo; Dr. Ashok Kumar Malik (Revista Electronica de Veterinaria, 2024)
across various sports disciplines. This study aimed to compare these three fitness components among individual and team sport athletes to understand how different sporting environments influence physical attributes. The research was conducted on 120 male athletes (60 from individual sports—wrestling, judo, and boxing, and 60 from team sports—hockey, football, and basketball) who had secured podium finishes in inter-collegiate competitions of Haryana universities. A survey and observation-based approach was used, and physical fitness was assessed using standardized tests: the 50-Yard Dash for speed, the Shuttle Run for agility, and the 600-Yard Run/Walk for endurance. Statistical analyses, including mean, standard deviation, and t-tests, were employed to determine differences between the two groups. Results revealed that team sport athletes demonstrated significantly superior speed (Mean: 5.800s vs. 6.663s; p < 0.0001) and agility (Mean: 8.628s vs. 10.078s; p < 0.0001) compared to individual sport athletes. This difference is attributed to the high-intensity, dynamic nature of team sports, which demand frequent directional changes and rapid acceleration. However, no significant difference was observed in endurance (Mean: 96.62s vs. 96.78s; p = 0.8366), suggesting that both groups develop similar aerobic capacities due to the endurance requirements inherent in their respective sports. The findings reject the null hypotheses for speed and agility but accept it for endurance. These insights can help coaches and trainers develop sport-specific training programs to enhance performance based on the unique physical demands of each sport. Future research should explore additional physiological and biomechanical factors to gain a more comprehensive understanding of athletic performance across different sporting disciplines.